Peacemongers. - Hill, Barry (University of Queensland Press, 2014)
A literary masterpiece, this latest book from award-winning author Barry Hill is a travel book, a history book, and a peace book. His odyssey begins with a pilgrimage to Bodhi Gaya in India, where the Buddha received enlightenment, and ends after he reaches Nagasaki, Japan, in the aftermath of its atomic bomb. His traveling is imbued with the life and ideas of India's greatest artist and intellectual, Rabindranath Tagore, along with that of M.K. Gandhi, who Tagore called "Mahatma," Great Soul. He's then traveling, like Tagore, in Japan, and meditating on its militarist turn, its warmongering